Diffuse Large B-Cell Lymphoma (DLBCL) of the Mesocolon in A Young Man with Intussusception: A Case Report - Laksmi, Lidya Imelda; Muhar, Adi Muradi; Hasibuan, Winda Syahfitri (Indonesian Journal of Cancer, 2026)
Introduction: Diffuse Large B-cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma (NHL), accounting for 25% to 30% of NHL cases. Diffuse large B-cell lymphoma (DLBCL) commonly happens in the seventh decade and often arises in the lymph nodes but can also present as an extra nodal disease. Nodal DLBCL involves the lymph nodes and does not involve the organ under the lymph nodes. In this case, we want to report a case of 25 men diagnosed with intussusception caused by nodal mesocolon enlargement, and histomorphology examinations revealed that the nodal enlargement is DLBCL. Here we reported a case of 25 years old man diagnosed with invagination caused by nodal mesocolon enlargement and, histomorphology examinations revealed the nodal enlargement is DLBCL.Case Presentation: We reported a case of 25 years old man complaints nausea, vomiting, abdominal pain, and was diagnosed with intussusception. Macroscopic examination showed nodal enlargement without colon mucosal involvement. Microscopic examination showed a relatively uniform and monotonous distribution of lymphoid cells with large cell sizes, enlarged nuclei with a round to oval shape, vesicular chromatin, amphophilic cytoplasm and some foci of tumour cells arranged in loose stroma. Macrophage and atypical mitoses were found. Immunohistochemical examination results were as follows: CD 117 (-), DOG 1 (-), CK (-), CD 45 (+), Myogenin (-), MyoD1 (-), CD20 (-), CD3 (-), Ki67 50%, CD 20 (+), CD3 (-), CD 10 (-), BCL6 (-), MUM1 (+).Conclusion: Diffuse large B-cell lymphoma (DLBCL) can occur in gastrointestinal as extra nodal lymphoma. The mesocolon contains many lymph nodes, but gastrointestinal lymphoma usually involves the gastrointestinal tissue. This case reports a case of 25 years old man who presents with intussusception caused by DLBCL in nodal mesocolon without colon involvement.